Empirical Analysis of Islamic Financing: PLS and Non-PLS Impacts on Real Sector - Rifki Botutihe; Aldiwanto Landali (Talaa : Journal of Islamic Finance, 2025)
The main focus of this study is to understand why, despite PLS-based financing's advantages in terms of fair risk sharing and supporting long-term economic growth, its implementation is still limited compared to non-PLS schemes, which are considered simpler and less risky. Using an empirical approach based on data from Sharia financial institutions, this study assesses the relative contribution of the two financing models to real economic activity. The analysis was conducted through a comparison between PLS-based instruments, such as mudarabah and musharakah, with non-PLS instruments, such as murabahah, ijarah, and istishna. The result showed that PLS-based financing had a stronger positive influence on the real sector because it encouraged productive investment and fair risk sharing between funders and entrepreneurs. In contrast, non-PLS financing tended to be more dominant due to its lower risk and simpler operational mechanisms, but its link to real economic growth is relatively weaker. This study concludes that increasing the share of PLS-based financing can strengthen the sustainability and inclusiveness of the Islamic financial system. These findings offered important implications for policymakers, regulators, and practitioners in formulating strategies to strengthen the role of Islamic finance in sustainable real sector development.